Strategi Manajemen Pemasaran dalam Meningkatkan Minat Peserta Didik Baru di MA Al-Furqon Cimerak - Rizal Yulianto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to examine marketing management strategies in increasing the interest of new students at MA Al-Furqon Cimerak. This study used a qualitative approach with a descriptive method to describe phenomena that occur naturally. Data collection was carried out through field research with observation, interview and documentation techniques. The data sources consist of primary data obtained from respondents, as well as secondary data derived from document and archive data. This research focuses on the promotion strategy implemented by MA Alfurqon Cimerak to increase the interest of prospective new students. Based on the results of an interview with the principal, Imam M. Kapapih S.Pd, promotion is an important part of the marketing of educational institutions because it functions as a communication tool that can bring together customer needs with the services offered by the school. MA Afurqon uses various promotions, both directly through junior high schools/MTs and approaches to teachers, as well as indirectly through print and online media. In addition, MA Al-Furqo promotes the excellence of programs such as the Tadarus of the Quran and achievements in the academic and non-academic fields as the main attraction. Word of mouth promotion is also used by involving alumni who provide positive recommendations. This strategy is designed to introduce the school to the wider community and attract the interest of prospective new students. In this way researchers are interested in talking the title marketing management strategy in increasing the interest of new students at MA Al-Furqon Cimerak.